Fenomena Thrifting Yang Populer Dikalangan Mahasiswa - Nika Nencyana Fadila; Raudhotul Alifah; Andhita Risko Faristiana (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2023)
In this day and age, the phenomenon of thrifting is not new but is gaining popularity among young people, especially college students. At present, fashion is a necessity whose development is very fast with the emergence of various new fashion trends among teenagers in a short period of time. One of them is fashion thrift. Thrifting itself is a used-goods shopping activity that aims to save costs. The reason why thrifting is currently very popular and popular with teenagers, especially students, is that by spending a minimum of money, you can get items of various models, and you can even find items that are classified as rare. This causes a feeling of self-satisfaction. Another reason for the fashion thrift phenomenon that is happening in Indonesia is the lifestyle of people who want to look fashionable with a minimal and appropriate budget due to a sense of prestige. This phenomenon is quite interesting and is a strong reason for researchers to research the thrifting phenomenon to explore further the perspectives of students regarding the thrifting phenomenon, what factors have caused this phenomenon to become popular again, what are the interesting things for students about the thrifting phenomenon, and product quality as well as the impact of usage on consumers. Researchers used a qualitative approach with literature study and analysis techniques.